Some New CARISTI Type Results in Metric Spaces with an Application to Graph Theory - Adilakshmi, G.; N.V.Kishore, G.; Sridhar, W. (International Journal of Engineering and Technology, 2018)
In this paper we proved some new Caristi type common fixed point theorems for four maps in a metric space and we gave an applications to Graph theory.Â Â